Cytogenetic and cytological analysis of advanced genetic material of cape gooseberry Physalis peruviana for use in plant breeding - CLARA VIVIANA FRANCO FLOREZ (Firenze University Press, 2021)
The cape gooseberry, Physalis peruviana L., is a crop that is transitioning from a semi-wild rural food source to becoming an international export commodity fruit deserving of greater attention from the scientific community, producers, policy makers and opinion makers. Despite its importance, the crop has serious technological development challenges, mainly associated with the limited supply of genetically improved materials for producers and consumers. In the present study, the level of ploidy of 100 genotypes of gooseberry from a working collection was determined by counting the number of chromosomes and chloroplasts, to include them in the breeding program. The number of chromosomes in dividing cells of root-tip meristems, as well as the number of chloroplasts per guard cell, from plants grown in vitro and ex vitro conditions were determined. Haploid with 24 chromosomes, doubled haploid-tetraploid with 48 chromosomes, aneuploid (44 and 49 chromosomes) and mixoploid genotypes with 36 to 86 chromosomes were found. The number of chloroplasts / cell guard ranged from 4-8, 6-16, 7-16 and 9-21 for the haploid, aneuploid, doubled haploid-tetraploid and mixoploid genotypes, respectively. Evidence of a high cytogenetic diversity in the evaluated genotypes.